Analysis Of The Management And Utilization Of The National Health Insurance Capitation Fund (JKN) Puskesmas In Deli Serdang Regency - Oktapianti, Wanda Aulia; Dwi Melisa Putri; Indah Doanita Hasibuan; Restu Malia Mazid; Nabila Wulandari (Jurnal EduHealth, 2024)
This study discusses the analysis of the management and utilization of the National Health Insurance (JKN) capitation fund at the Puskesmas in Deli Serdang Regency. The research method used was an in-depth interview and qualitative approach at 3 puskesmas in Deli Serdang Regency, namely Gunung Tinggi Health Center, Kutalimbaru Health Center and Bandar Baru Health Center. The results show the effectiveness and efficiency of capitation fund management practices at the puskesmas, with strict supervision in accordance with applicable regulations. Capitation funds are used to pay for health care services and operational costs. The Puskesmas studied has also used JKN capitation funds in accordance with the specified percentage, but several aspects need to be considered to ensure better compliance. Suggestions for improving the effectiveness of the use of capitation funds include capacity building and training related to capitation fund management.